Lean-environmental management system integration model - Vasu, Suresh (2014)
Environmental management system (EMS) is a tool for managing the impact of an organization’s activities on the environment. The most well-known EMS model is ISO 14001. ISO 14001 is touted as the most successful global environmental standard which provides the framework to control and reduce impact on the environment. Although the standard believed to be one of the best environmental management model, there are studies reveal that industries are currently facing a number of challenges to maintain competitiveness, productivity and minimal environmental impact. Besides that, studies also shows that the standard lack of guidelines to accomplish “continuous improvement” element, operational definition on continuous improvement and method to assess it. This turns to be the main factor influence the standards sustainability. Lean is a tool for process improvement focusing on key processes that affect the output to the customer and focuses on continuously improving the process management elements. Lean pushes for continuous improvement and empowers companies to better their environmental performance. The purpose of this study is to integrate lean principles with ISO 14001 standard to achieve sustainability through continuous improvements. Three objectives were identified to achieve this purpose. First objective, identify both system’s characteristic through literature review and questionnaire survey, then continue with the second objective, find the linkages between both system and develop an integration model and finally the third objective, validate the model using focus group. This study uses combination of qualitative and quantitative research methodology. Reliability test and descriptive statistics using statistical package of the social science software were used to record, analyze and interpret the raw rata. Finding shows that there is positive correlation between both systems; as a result, new model called Lean Environmental Management Integration System (LEMIS) has been developed. The model creates measurement standards for evaluating the organization, making its environmental efforts more realistic, focused and attainable. The model’s validation results shows that by integrating the standard with Lean principles through LEMIS model helps to specify the performance measures and leads the standard to achieve sustainability and continuous improvement. This study presents a unique approach of integrating the two main models as a single framework benefiting contemporary organizations. The study concludes by stating that more case studies in this direction are required to be conducted for examining the feasibility of amalgamation and implementing ISO 14001:2004 standards with the philosophy of Lean Principles to enable the achievement of world class standards.